Una Dieta saludable para segundo grado - Paredes Alvarado, José Carlos (2018)
The area of Science Technology and Environment aims to develop in students the construction of scientific, critical and technological thinking, as well as the development of competencies that condition to question and investigate situations in the environment that can improve the quality of life, "inquires through scientific methods "," explains the physical world "," designs and produces technological prototypes "," builds a critical position ". In this way, the development of competencies that encourage the exercise of critical thinking in students is encouraged._x000D_ With the theme "A HEALTHY DIET" we will achieve that our students value in their own flesh their food that they eat every day in their diet.